Spatial differences in the level of population and settlement development in Wielkopolskie voivodship (1) - Konecka-Szydłowska Barbara; Maćkowiak Henryk (Bulletin of Geography. Socio-Economic Series)
Population and settlement are among aspects determining the level of socio-economic development. This paper analyses spatial differences in the level of development of the population and settlement in Wielkopolskie voivodship in Poland. The period studied embraces the years 2000-2010 and the units examined are those of the local NUTS 4 level, i.e. poviats.